2015
DOI: 10.1111/1475-6765.12125
|View full text |Cite
|
Sign up to set email alerts
|

Party debate over Europe in national election campaigns: Electoral disunity and party cohesion

Abstract: Abstract. Few political parties are willing to lead the public debate on how the European Union should develop and parties rarely publicly discuss issues on the EU agenda. This is probably one of the most important democratic problems in the contemporary EU. When and why parties are willing (or not willing) to discuss European cooperation is therefore an essential issue in which political science should engage. Previous research has shown that parties that are internally divided on EU issues downplay these iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…: 10). A similar mechanism has been identified in political parties divided on the issue of Europe: before an election, when vote‐seeking becomes the dominant motivation and inconsistent messaging a risk to success, the leadership suppresses intraparty conflict more effectively (Hellström & Blomgren : 268, 269, 279). Evidence of intensifying national control before European elections also comes from the formal analysis of legislative voting in EP5 (Lindstädt et al.…”
Section: When Politics Trumps Loyalty: An Explanatory Frameworkmentioning
confidence: 72%
“…: 10). A similar mechanism has been identified in political parties divided on the issue of Europe: before an election, when vote‐seeking becomes the dominant motivation and inconsistent messaging a risk to success, the leadership suppresses intraparty conflict more effectively (Hellström & Blomgren : 268, 269, 279). Evidence of intensifying national control before European elections also comes from the formal analysis of legislative voting in EP5 (Lindstädt et al.…”
Section: When Politics Trumps Loyalty: An Explanatory Frameworkmentioning
confidence: 72%
“…A study of Steenbergen and Scott (2004) suggested that parties that are internally divided on Europe aim to de-emphasise the issue. This strategy will be successful insofar as the intensity of the internal dispute over EU issues is moderate and can be tamed by the party leadership (Hellström and Blomgren, 2016).…”
Section: Brexit and The Politicisation Of European Integrationmentioning
confidence: 99%
“…Opposition to European integration has been driven by new challenger parties from the radical left and the radical right, while established parties have resorted to a vast array of strategies to depoliticise European integration in national politics (De Wilde and Zürn, 2012; Green-Pedersen, 2012; Hooghe and Marks, 2018; Schimmelfennig, 2018). To be sure, mainstream parties have not always succeeded in their attempts to depoliticise the issue (Dolezal and Hellström, 2016; Hellström and Blomgren, 2015), as is vividly illustrated by the British Conservatives, but they have generally attempted to keep it off the agenda. Given that opposition to European integration has come both from the radical left and the radical right suggests that the answer to the question is not an unambiguous one: while the Euroscepticism from the radical right qualifies for ‘backlash politics’, the Euroscepticism from the radical left does not at first sight, although it also shows some traces of this kind of politics.…”
Section: What Kind Of Backlash Politics?mentioning
confidence: 99%